"Prakata dan Pra Isi" Buku Siswa Kelas I Berdasarkan Kelayakan Buku BNSP dan EYD Edisi V - Afina Hafiyyan N; Panca Dewi Purwati; Claresta M. R; Syakira N. A; Gading W. A. (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This research tackles the important matter of the quality of textbooks by examining the introductory and concluding sections of the Indonesian language textbook "Aku Bisa! (Revised Edition)" in relation to the guidelines set by the National Education Standards Agency (BSNP). The main goal is to assess how well the textbook conforms to the four key criteria defined by BSNP: content, presentation, language, and illustrations. To conduct this assessment, a descriptive qualitative approach, specifically content analysis, was utilized gathering data through the review of relevant documents. The results show that although the preface generally satisfies the clarity standards concerning the book's aims and relevance to the curriculum, it falls short in providing detailed guidance on how the book should be used by both students and teachers. The pre-content parts, such as the table of contents and instructions for use, are mostly organized, but there is room for improvement to enhance the connection between the content and the numbering of the chapters. In summary, the textbook is found to be viable, with some minor adjustments suggested for its presentation and language aspects. The study concludes that "Aku Bisa!" mostly complies with BSNP standards regarding its pre-content and preface, although additional work on how information is presented and the overall structure is needed to enhance its teaching effectiveness.